Pediatric Acute Stroke Protocol Activation in a Children's Hospital Emergency Department. Issue 8 (August 2015) - Ladner, Travis R.; Mahdi, Jasia; Gindville, Melissa C.; Gordon, Angela; Harris, Zena Leah; Crossman, Kristen; Pruthi, Sumit; Abramo, Thomas J.; Jordan, Lori C.
<x xml:space="preserve">Abstract</x> Background and Purpose— Pediatric acute stroke teams are a new phenomenon. We sought to characterize the final diagnoses of children with brain attacks in the emergency department where the pediatric acute stroke protocol was activated and to describe the time to neurological evaluation and neuroimaging. Methods— Clinical and demographic information was obtained from a quality improvement database and medical records for consecutive patients (age, ⩽20 years) presenting to a single institution's pediatric emergency department where the acute stroke protocol was activated between April 2011 and October 2014. Stroke protocol activation means that a neurology resident evaluates the child within 15 minutes, and urgent magnetic resonance imaging is available. Results— There were 124 stroke alerts (age, 11.2±5.2 years; 63 boys/61 girls); 30 were confirmed strokes and 2 children had a transient ischemic attack. Forty-six of 124 (37%) cases were healthy children without any significant medical history. Nonstroke neurological emergencies were found in 17 children (14%); the majority were meningitis/encephalitis (n=5) or intracranial neoplasm (n=4). Other common final diagnoses were complex migraine (17%) and seizure (15%). All children except 1 had urgent neuroimaging. Magnetic resonance imaging was the first study in 76%. The median time from emergency department arrival to magnetic resonance imaging was 94 minutes (interquartile range, 49–151 minutes); the median time to computed tomography was 59 minutes (interquartile range, 40–112 minutes). Conclusions— Of pediatric brain attacks, 24% were stroke, 2% were transient ischemic attack, and 14% were other neurological emergencies. Together, 40% had a stroke or other neurological emergency, underscoring the need for prompt evaluation and management of children with brain attacks.